From local to global and informal to formal: Entering mainstream markets - Reema Nanavaty (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2005)
This is a brief sketch of the Self Employed Women's Association's (SEWA) threedecade- long journey from the local to global and informal to formal sector in search of finding work and income for now 720,000 women workers. Though SEWA remains a local and an informal economy workers' organization, its aim has always been to mainstream its issues, hopes, and achievements.
Keywords: D02; E26; O17; P13; Q13; 330; women; informal economy; cooperative; India; poverty; institutions; Informeller Sektor; Frauenerwerbstätigkeit; Armut; Indien